Pengaruh Sosialisasi, Kondisi Sosial Ekonomi, serta Dukungan Pemerintah Terhadap Adopsi Inovasi Pengelolaan Sampah Organik: The Effect of Socialization, Socio-Economic Conditions and Governemnt Support on The Adoptionof Organic Waste Innovation - Ferdial Ferdial; Sri Listyarini; Lina Warlina (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2023)
Successful of organic waste management is closely related to the adoption of innovation by the community. This study aims to see the effect of socio-economic conditions, socialization and government support to the adoption of organic waste management innovation. Research location was in Perak Utara Village, Pabean Cantikan District, Surabaya for 100 respondents. Independent variables are socialization programs, socio-economic conditions and government support while innovation adoption is the dependent variable. Data was obtained through a questionnaire. Data analysis used SPSS 25.00 for windows. Through linear regression analysis, the influence of independent variables consists of socialization program (X1), socio-economic conditions (X2) and government support (X3) on the dependent variable adoption of innovation (Y) are obtained by equation: Y' = -0.830 + 0.525X1 + 0.132X2 + 0.610 X2 + e. Without good social economic conditions (X1 = 0), no outreach program (X2 = 0) and without government support (X3 = 0) will have a negative effect on innovation adoption. Determination analysis shows the influence of independent variables to the dependent variable is 63.1% or socialization program, socio-economic conditions and government support are able to explain 63.1% of the innovation adoption, while remaining 36.9 % is influenced by other variables outside of this study.